Immobilization of Peroxidase on Functionalized Multi-walled Carbon Nanotube Buckypaper/Polyvinyl Alcohol Membrane for Dye Wastewater Treatment - Lau, Yien Jun (Curtin University, 2020)
This research develops a novel system of agriculture waste peroxidase immobilized onto buckypaper/polyvinyl alcohol membrane for dye wastewater treatment in a multi-stage membrane column. The membrane support exhibited high enzyme immobilization efficiency of 81%, owing to its large surface-area-to-volume ratio and excellent physiochemical properties. Compared to free peroxidase, immobilized enzyme has shown significant improvement in enzymatic activity and its storage stabilities. The system demonstrated scalability and commercial feasibility with almost complete dye removal efficiency.